Attitudes of Physical Education Teachers towards Inclusion of Students with Disabilities in the Physical Education Classes in Albadia Alwosta Schools - Al-Jbour, Aws; Al-Shaar , Amer; Al-Sarhan , Sara; Al-oran , Hasan; Al-Rahamneh, Harran (Dirasat: Educational Sciences, 2023)
Objectives: This study aims to assess the attitudes of physical education teachers towards the inclusion of students with disabilities in the physical education classes in Albadia Alwosta schools. Methods: The descriptive approach was employed and a questionnaire consisting of (26) items divided into two domains (i.e, educational field and psychosocial field) was developed. Validity and reliability were checked before data were collected. The study sample consisted of (94) physical education teachers of Albadia Alwosta schools who were selected randomly from the study population. The study classified the attitudes into three levels (i.e., 1.00 – 2.33 low, 2.34 – 3.67 moderate and,3.68 – 5.00 high). Results: The results showed that the attitudes of physical education teachers towards the inclusion of students with disabilities in the physical education classes in Albadia Alwosta schools were moderate (3.62 ± 0.52). The psychosocial field was the first (3.84 ± 0.62) and the educational field was the last (3.40 ± 0.56). The results also showed that there were no significant differences between male and female teachers and between teachers of different experiences in the attitudes toward the inclusion of students with disabilities in physical education classes. Conclusions: The study recommended training physical education teachers and developing their abilities and skills through courses and workshops during and pre-service to work with students with disabilities appropriately in physical education classes.